Sexting motive on sexting behaviours among emerging adults in Malaysia: The moderating role of gender and relationship status - Goh, Yee Shan (2023)
Although the media has been negatively portraying sexting behaviour, yet it remains prevalent among people across countries. The recent lockdown due to the COVID-19 pandemic makes sexting behaviours an even more viable option for satisfying individuals' sexual desires. Local studies on sexting are limited, but evidence depicted an increasing engagement in this behaviour. Despite the fact that sexting behaviour is regularly associated with negative consequences, the motivations that keep people sexting are unknown among Malaysian emerging adults. This study seek to identify the engagement level in sexting behaviour in Malaysia. It also seeks to examine the sexting motives, gender, and relationship status differences, as well as the moderating role of gender and relationship status between sexting motives on sexting behaviour. This crosssectional quantitative study recruited participants using the purposive sampling technique during the pandemic period from August to October 2020. A total of 252 emerging adults (Mage = 22.84; SD = 2.05), with 55.7% being females, participated in the study. The result depicted that 88.1% of participants ever sexted with someone. The independent sample t-test analysis showed that males and participants in-relationship were more likely to sext compared to females and singles. Hierarchical multiple regression depicted that intimacy, enhancement, and peer pressure significantly predicted sexting behaviour. Gender does not moderate the association between all motives and sexting II behaviour. Meanwhile, relationship status moderates the associations of selfaffirmation and peer pressure on sexting behaviour. Findings have shed new light and bridged the knowledge gap on sexting behaviour among Malaysian emerging adults that serve as an informative input for the future revision of sexual reproductive health education implementation.